PEMANENAN GETAH PINUS MENGGUNAKAN TIGA CARA PENYADAPAN - Sukadaryati (Jurnal Penelitian Hasil Hutan, 2014)
Pine resin is one kind of non wood forest products (NWFP) that has passably potency and Indonesia occupies thirdrank in the world as a producer pine resin after China and Brazil. The good market opportunity of gondorukem pushedmanagement of forest to increase pine resin production. This paper aims to give information about harvesting of pine resinusing three tapping techniques. The tapping techniques depends on tapping tool is used, namely mujitech, drill and kedukul.The results showed that the highest production of resin was obtained from the technique using kedukul, 18.0g/quare/collection whereas from Mujitech dan drill was 11.5 g/quare/collection and 11.2 g/quare/collectionrespectively. From visual observation, resin obtained by drill technique was cleaner than Mujitech and kedukul techniques.The content of impurities in pine resin that produced by drill technique was 4% on average. Nevertheless, drill tappingtechnique is not preferred by farmers to apply as less effective.The application of tapping techniques at a certain location were influenced by the customs of the local communities.And those customs were not easy to be changed with new technique although that can produce the tapping more thanmanually technique.